Policing Non-Violent Crowds: Lessons from Kumbh Mela in India. (15th March 2018) - Verma, Arvind; Varma, Vinayak
Abstract: Crowd control by police has been generally studied in the context of violence involving protestors and demonstrators. However, nonviolent crowds also pose equal challenges for the police. Major sporting events, musical festivals, religious and political celebrations attract large crowds that need sensitive policing. Nevertheless, policing tactics for the two situations are generally similar. Research on public order policing has relevance and lessons for policing of large non-violent crowds too. This paper presents a case study of police management of Ujjain Kumbh Mela, which attracts millions at one place for a religious ritual. We analyze characteristics of the crowd and strategies adopted by the police based upon extensive field data of the recent event of 2016. This study suggests that the Indian police, unaware of the research on public order policing followed many of the lessons reported in public order policing in western societies. We contend that experience and practice counts, but by institutionalizing research as part of its organization the Indian police could enhance it capabilities to handle serious challenges that confront it on a daily basis. Lessons for handling non-violent crowds in democratic societies are also drawn.